2022
DOI: 10.1101/2022.06.07.494774
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Formation of protein-mediated bilayer tubes is governed by a snapthrough transition

Abstract: Plasma membrane tubes are ubiquitous in cellular membranes and in the membranes of intracellular organelles. They play crucial roles in trafficking, ion transport, and cellular motility. The formation of plasma membrane tubes can be due to localized forces acting on the membrane or by curvature-induced by membrane-bound proteins. Here, we present a mathematical framework to model cylindrical tubular protrusions formed by proteins that induce anisotropic spontaneous curvature. Our analysis revealed that the tub… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…To understand the interaction between CL, which contributes to net membrane spontaneous curvature, and ATP synthase oligomers, whose induced curvature is localized specifically at cristae ridges, we employed a continuum modeling framework based on previous efforts to model membrane tubule formation (Mahapatra & Rangamani, 2023). We modeled the simplest CM structure—tubules—as axisymmetric tubes that bud from a flat membrane (Fig 5A).…”
Section: Resultsmentioning
confidence: 99%
“…To understand the interaction between CL, which contributes to net membrane spontaneous curvature, and ATP synthase oligomers, whose induced curvature is localized specifically at cristae ridges, we employed a continuum modeling framework based on previous efforts to model membrane tubule formation (Mahapatra & Rangamani, 2023). We modeled the simplest CM structure—tubules—as axisymmetric tubes that bud from a flat membrane (Fig 5A).…”
Section: Resultsmentioning
confidence: 99%
“…To understand the interaction between CL, which contributes to net membrane spontaneous curvature, and ATP synthase oligomers, whose induced curvature is localized specifically at cristae ridges, we employed continuum modeling framework based on previous efforts to model membrane tubule formation 73,103105 . We modeled the simplest CM structure — cristae tubules — as axisymmetric tubes that bud from a flat membrane (Figure 5A).…”
Section: Resultsmentioning
confidence: 99%
“…via CL-encoded membrane spontaneous) was increased for a fixed value of anisotropic curvature (Figure 5Cii) for the different values of bending moduli (see also Figure S5 for additional simulations). This sudden change in length is characterized by a snapthrough transition, where a small amount of thermodynamic work done on the system, by changing either material properties or curvatures induced, results in a change in the minimal energy state of the system where a tube-like shape is a low energy configuration 103,104,108,109 . We observed that the curvature values at which this transition occurs was modulated by the presence of a collar force at the tubular neck, suggesting that mechanics could underlie the functional interactions observed between Mic60p at the CJ and PL saturation (Figure S2C, Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…Mathijs et al considered a Ginzburg-Landau-type free energy for the protein coat and discussed the stability of the cylindrical tubes covered with proteins [19]. Mahapatra and Rangamani developed a theoretical model to estimate the free energy of membrane tubulation due to bound BAR-domain proteins with anisotropic curvature, and showed the snapthrough characteristics in the dome-to-cylinder transitions [20] Here we offer a fresh take on this problem, using a mesoscopic dynamical membrane model [21]. We had previously shown this model to reproduce realistic kinetics attributed to membrane fluctuations [22,23] as well as lateral diffusion of membrane-bound peripheral proteins [24].…”
Section: Introductionmentioning
confidence: 99%
“…Mathijs et al considered a Ginzburg-Landau-type free energy for the protein coat and discussed the stability of the cylindrical tubes covered with proteins [19]. Mahapatra and Rangamani developed a theoretical model to estimate the free energy of membrane tubulation due to bound BAR-domain proteins with anisotropic curvature, and showed the snap-through characteristics in the dome-to-cylinder transitions [20]. While these studies are quite illuminating, they usually ignore membrane-protein interplay in a dynamical setup, and thus, provide limited information on the kinetics of the tubulation process.…”
Section: Introductionmentioning
confidence: 99%